An Al‐inducible expansin gene, OsEXPA10 is involved in root cell elongation of rice. (22nd September 2016) - Che, Jing; Yamaji, Naoki; Shen, Ren Fang; Ma, Jian Feng
Summary: Expansins are cell wall loosening proteins, which are encoded by multigene families. However, the physiological role of most expansin genes is still poorly understood. Here, we functionally characterized an Al‐inducible expansin gene, OsEXPA10, which is regulated by a C2H2‐type zinc‐finger transcription factor, ART1 in rice. A detailed expression analysis showed that OsEXPA10 was expressed in both the roots and shoots at a similar level, but only the expression in the roots was rapidly upregulated in response to Al. Furthermore, spatial expression analysis showed that the Al‐induced expression was only found in the root tips (0–3 mm), but not in the mature root zones. The expression was neither induced by other metals including Cd and La nor by low pH. Immunostaining showed that OsEXPA10 was localized at all cells of the root tips. Knockout of OsEXPA10 resulted in a significant decrease in the cell elongation of the roots in the absence of Al. In the presence of Al, knockout of OsEXPA10 did not alter the Al sensitivity evaluated by relative root elongation, but the root cell wall of knockout lines accumulated less Al compared to those of the wild‐type rice. Collectively, our results indicate that OsEXPA10 expressed in the root tips is required for the root cell elongation, but that the contribution of this gene to high Al tolerance in rice is small. Significance Statement: Expansins are cell wall‐loosening proteins encoded by multigene families, but the physiological role of most expansins are poorly understood. Here we show that an aluminum‐inducible expansin gene, OsEXPA10, is important for root cell elongation but makes little contribution to aluminum tolerance.